Dynamics Of Political Parties And Elections In The Modern Democracy Era - Hafidz Zakiyuddin; Dinar Widia; Andika Handoko; Khikmawanto Khikmawanto (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2023)
This journal analyzes the dynamics of political parties and elections in the context of the modern democratic era. The research uses a qualitative approach and explores how political parties adapt to social and political changes, as well as influence the general election process. The results show the challenges of political parties in maintaining internal unity, facing intense political competition, and responding to the aspirations of increasingly intelligent voters. Transparency and public participation are also key in maintaining the quality of democracy in the modern era.